A REVIEW ON AUTOMATIC DOOR OPENING TECHNIQUES AND METHODS FOR PRODUCT TESTING - Sanjay G.Godase; Prof.A.K.Mahindrakar (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper is reviewing the different techniques and methods used for a Refrigerator door opening for product testing. This System will be used for the replicating customeruses pattern of refrigerator at test lab, to evaluate refrigerators actual field performance, during development stage of the product. Due to resource optimization, safety, reduced operating cost and lead time, accuracy in repeated task, the automation ishighly recommended in the industries. Comparison for suitable techniques for this system are described in this paper, also to evaluatefurther,proposedsystemisdescribedinbrief.